Integrating Multiple Intelligences into the Islamic Education Curriculum: A Case Study in an Integrated Islamic School - Aziz, Tariq; Amirudin, Amirudin; Arifudin, Yadi Fahmi (Jurnal Cendekia Media Komunikasi Penelitian dan Pengembangan Pendidikan Islam, 2025)
The purpose of this study is to describe the form of integration of multiple intelligence in the learning of Islamic Religious Education at Buahati Islamic Elementary School Karawang, analyze its impact on student motivation and engagement, and identify the challenges and strategies used by schools in their implementation. The research uses a qualitative approach with case study methods through in-depth interviews, participatory observations, and documentation. Data analysis is carried out interactively through reduction, presentation, and drawing conclusions by triangulating sources and methods. The results of the study show that the integration of multiple intelligence in the learning of Islamic Religious Education at Buahati Islamic Elementary School Karawang increases student motivation, participation, and understanding through learning activities that are tailored to their intelligence profile. This study found that the integration of multiple intelligences in Islamic Religious Education learning was carried out through differentiated planning, mapping of student intelligence, and the use of learning activities that stimulated eight intelligences. The impact can be seen in increasing motivation, participation, focus on learning, and students' courage in discussing. In addition, multi-intelligence-based learning helps reinforce the internalization of religious values through hands-on experience. The research also revealed challenges in teacher competence, time constraints, and uneven support facilities, even though schools have implemented various strategies such as internal training and collaboration between teachers. This research contributes to providing empirical evidence on the effectiveness of the multiple intelligence approach in religious learning and offers practical recommendations for the development of differentiated learning in integrated Islamic schools.